Digital Retail Transformation: The Influence of E-Commerce, Digital Marketing, and Service Quality on Purchasing Decisions - Ekel Jadi Lapenta Tarigan; Mega Ruslina Safutri; Yolanda Salsabila; Ricky Rafii Ritonga; Zenni Riana (STIE Amkop Makassar, 2026)
This study examines the effect of e-commerce, digital marketing, and service quality on purchasing decisions at PT Gramedia Asri Media, a retail company. The study employed a quantitative approach with descriptive and associative characteristics. The population consisted of customers of PT Gramedia Asri Media, based on 86,085 customer transactions. The sample was determined using the Slovin formula, and 120 respondents were obtained during the data collection process. Data were collected through a Likert-scale questionnaire distributed via Google Forms and were analyzed using multiple linear regression with IBM SPSS. The results showed that, partially, e-commerce had a positive and significant effect on purchasing decisions with a t-value of 2.731 and a significance value of 0.007, digital marketing had a positive and significant effect with a t-value of 2.652 and a significance value of 0.009, and service quality had a positive and significant effect with a t-value of 3.988 and a significance value of 0.000. Simultaneously, e-commerce, digital marketing, and service quality had a positive and significant effect on purchasing decisions with an F-value of 84.105 and a significance value of 0.000. The Adjusted R Square value of 0.677 indicated that 67.7% of purchasing decisions could be explained by the three independent variables, while the remaining 32.3% was influenced by other variables outside this study